Identifying and Categorizing Derivational Morphemes on Students’ Thesis Abstracts: A Corpus-Driven Analysis - Arbi, Anggun Purnomo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to analyze the use of derivative morphemes in thesis abstracts of STKIP PGRI Sidoarjo students, focusing on the contribution of these morphemes to the clarity and quality of academic writing. The problem raised is the lack of understanding of the role of derivative morphemes in academic writing. The method used is corpus-based analysis of five student thesis abstracts. The findings of this study show that derivative morphemes such as “-er”, “-ion”, and “-al” help in conveying information and clarifying the content of the abstract. The analysis identified how derivative morphemes contribute to the understanding of the content and structure of the research. In conclusion, a better understanding of the use of derivative morphemes can improve the quality of academic writing. Suggestions are given for the improvement of morphology learning curriculum at the higher education level, in order to strengthen students' writing skills.